EVALUATION OF NUTRITIONAL VALUE OF TWO LOCAL POTATO CULTIVARS (ABERCHAIBI AND AMUBI) OF MANIPUR, NORTHEAST INDIA - N. LOKENDRAJIT,; C. B. SINGH,; N. SWAPANA,; SINGH, M. SUMARJIT (The Bioscan, 2013)
Purple or red fleshed local potato cultivar (Solanum tuberosum Linn) was evaluated for their total phenolic, protein, carbohydrate and lipid contents. The total phenolic content of the local cultivar from the four districts of Manipur was found to be very high i.e. 263mg, 256mg, 270mg and 260mg per 100g of the dry weight. Significant differences were found between the purple or red fleshed and other varieties. There is not much variation in the fat content in the local cultivar and other varieties whereas the protein content is more than the average of the other genotype. Percentages of protein content in the four districts were 8.635, 8.124, 9.584 and 8.900 respectively. The cultivars were collected from four districts of Manipur, India. The indigenous people were using this potato during post-natal period and for diabetic patients too. The present work validates scientifically the information of the local indigenous people about the uses of this potato genotype in their day to day life.